Non-invasive physical plasma activates stimulator of interferon genes pathway in triple negative breast cancer and is associated with increased host immune response - Wang, Guilin; Arnholdt, Marcel; Koch, André; Enderle, Markus D.; Hahn, Markus; Brucker, Sara Y.; Weiss, Martin (Frontiers in Immunology, 2025)
Triple-negative breast cancer (TNBC), characterized by the absence of ER, PR, and HER2 receptors, remains one of the most aggressive breast cancer subtypes, with limited therapeutic options and a high relapse rate. While immune checkpoint inhibitors (ICIs) have shown promise by leveraging TNBC’s immunogenic profile, their use is often accompanied by significant toxicity, necessitating the development of safer immunomodulatory strategies. Non-invasive physical plasma (NIPP), a novel low thermal plasma technology that can be generated using various gases, including argon, and producing reactive oxygen and nitrogen species (RONS), has emerged as a potential alternative. This study investigates the capacity of direct (argon plasma devitalization, APD) and indirect (plasma-treated solution, PTS) plasma modalities to induce cytotoxicity and activate immune signaling via the stimulator of interferon genes (STING) pathway in TNBC. Dose-dependent RONS generation by APD and PTS correlated with reduced viability and apoptosis induction in MDA-MB-231 TNBC cells. Both plasma modalities caused DNA damage and upregulated key proteins in the STING pathway, including γ-H2AX, p-STING, and p-TBK1, with sustained activation observed up to 24 hours post-treatment. Furthermore, STING-dependent transcription of IFN-β and interferon-stimulated genes (ISGs) confirmed the immunogenic potential of NIPP. Conditioned media from plasma-treated TNBC cells induced M1 polarization in THP-1-derived macrophages, an effect significantly reduced upon specific STING inhibition with H-151. The immunomodulatory effects of NIPP were validated in patient-derived TNBC organoids, where plasma treatment disrupted organoid structure, reduced viability, and promoted M1 macrophage polarization. Collectively, these findings highlight the dual cytotoxic and immunostimulatory potential of NIPP in TNBC through STING pathway activation, claiming it as a promising, low-toxicity component in combination with conventional immunotherapy.